Tranexamic Acid Reduces Blood Loss and Blood Transfusion after TKA: A Prospective Randomized Controlled Trial - Charoencholvanich, Keerati; Siriwattanasakul, Pichet (Clinical orthopaedics and related research, 2011)
Background TKA may be associated with considerable blood loss, and transfusion carries substantial risk of immunologic reaction and disease transmission. Blood transfusion also involves additional cost, therefore a reduction in its use is important. Several methods reportedly reduce postoperative blood loss and avoid homologous blood transfusion with traditional TKA approaches, but it is unclear these reductions apply to a minimally invasive technique. Questions/purposes We asked whether tranexamic acid administration could reduce blood loss and blood transfusion requirements after TKA. Patients and Methods Between March 2008 and May 2008, we enrolled 100 patients with primary osteoarthritis undergoing a unilateral cemented TKA in a prospective, randomized, double-blind study. Patients were randomized into one of two groups: the control group received a placebo and the study group received tranexamic acid intravenously (10 mg/kg) 10 minutes before inflation of the tourniquet and 3 hours postoperatively and orally (250 mg/capsule; two capsules three times daily) for 5 days. We measured volume of drained blood 48 hours postoperatively, decrease in hemoglobin levels 12 hours postoperatively, amount of blood transfused, and number of patients requiring allogenic blood transfusion. The minimum followup was 6 months (mean, 10.4 months; range, 6–12 months). Results Mean (± SD) postoperative volume of drained blood was lower in the group receiving tranexamic acid (727.50 ± 234 mL) than in control subjects (1208.77 ± 421 mL). The mean hemoglobin decrease 12 hours postoperatively was lower in patients receiving tranexamic acid (2.12 ± 0.64 g/dL) than in control subjects (3.33 ± 0.88 g/dL). The amount of blood transfused and number of patients requiring blood transfusion were lower in patients receiving tranexamic acid than in control subjects. Conclusions Tranexamic acid reduced postoperative blood loss after TKA, as reflected in reduction in the number of blood transfusions. We did not observe any change in symptomatic thromboembolic phenomenon. Level of Evidence Level 1, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.